A Review of Mineral Carbonation from Industrial Waste. (November 2019) - Song, Xiao; Xiaoyu, Chen; Lin, Qi; Yanna, Liu
Abstract: For relieving CO2 emissions and climate change, carbon sequestration and storage has been paid more attention. Mineral carbonation technology is a process that the calcium and/or magnesium-containing minerals react with CO2 to form stable carbonate precipitation, which in turn fixes CO2 . It originates from natural rock weathering process that calcium and magnesium-containing rocks react with CO2 dissolved in rain water to form carbonate minerals. The source of mineral carbonation is the solid containing calcium and magnesium compound. The classification of mineral carbonation including direct and indirect mineral carbonation is indicated, and the descriptions of extraction by different extract agent have been given. The pretreatments, operation conditions and reaction kinetics are also discussed. Furthermore, the different processes by carbonizing from industrial waste are reviewed and the energy loss and cost are also described.